Molecular Characterization of Gram-Negative Bacilli Isolated from a Neonatal Intensive Care Unit and Phenotypic and Molecular Detection of ESBL and Carbapenemase - Barbosa, Thaís Alves [UNESP]; Bentlin, Maria Regina [UNESP]; Rugolo, Ligia Maria Suppo de Souza; Lyra, João César [UNESP]; Ferreira, Adriano Martison [UNESP]; Santos, Ana Cláudia Moro Lima dos; Teixeira, Nathalia Bibiana [UNESP]; Romero, Letícia Calixto Medeiros [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Cunha, Maria De Lourdes Ribeiro De Souza Da (MDPI, 2025)
INTRODUCTION: The increase in the rates of multidrug-resistant bacteria in healthcare environments has been recognized as a global public health problem. In view of the scarcity of data on the neonatal population, this study aimed to provide information on the genotypic and epidemiological characteristics of Gram-negative microorganisms isolated from colonization and infection sites in neonates admitted to a tertiary university center of high complexity. METHODS: Enterobacterales and non-fermenting Gram-negative bacilli previously collected in a prospective cohort study were submitted to genotypic identification, detection of extended-spectrum β-lactamases (ESBL), carbapenemases and biofilm production, detection of specific virulence markers in Pseudomonas aeruginosa, and typing by pulsed-field gel electrophoresis. RESULTS: The data found here revealed higher rates of infection by Klebsiella spp. and Serratia marcescens that caused bloodstream infection and pneumonia, respectively. In this study, high biofilm production was observed, with 95.0% of Enterobacterales and 100% of non-fermenting Gram-negative bacilli being producers. Most of the P. aeruginosa isolates carried pathogenicity factors such as alginate, hemolytic phospholipase C, exotoxin A, and rhamnolipids. The phenotypic analysis of ESBL revealed that 16 (5.3%) isolates produced these enzymes. Four of these isolates (66.7%) carried the CTX-M-9 gene, three (50%) carried the TEM gene, and one (16.7%) was positive for the SHV and CMY-2 genes. Univariate and multivariate Cox regression analyses were used to identify risk factors for colonization and infection by Gram-negative microorganisms. The results of multivariate analysis revealed that biofilm production by these microorganisms was associated with the persistence of colonization by the same pathogen in the newborn and increased by 75% the daily probability of the newborn developing infection. The production of ESBL also increased the daily probability of infection by 46.8 times. CONCLUSIONS: Enterobacterales showed average biofilm production, while the majority of non-fermenting Gram-negative bacilli were strong producers. The present data increase our knowledge of the molecular epidemiology of important Enterobacterales species, with emphasis on ESBL-producing Enterobacter cloacae and Klebsiella pneumoniae with emerging epidemiological potential in the neonatal intensive care unit of a tertiary university hospital. Furthermore, the results highlight the need for the monitoring and implementation of control measures and for restricting the use of broad-spectrum antibiotics.